Numerical Methods in Engineering and Science : C, C++, and MATLAB - Grewal, Bhajan S. (Bhajan Singh) (Mercury Learning, 2019)
Intended as an introduction to numerical methods for scientists and engineers, this book provides an excellent balance of theoretical and applied topics and shows the numerical methods used with C, C++, and MATLAB. --